2003
DOI: 10.1016/s0042-6822(03)00419-7
|View full text |Cite
|
Sign up to set email alerts
|

HCV core/gC1qR interaction arrests T cell cycle progression through stabilization of the cell cycle inhibitor p27Kip1

Abstract: Hepatitis C virus (HCV) is efficient in the establishment of persistent infection. We have previously shown that HCV core protein inhibits T cell proliferation through its interaction with the complement receptor, gC1qR. Here we show that HCV core-induced inhibition of T cell proliferation involves a G(0)/G(1) cell cycle arrest, which is reversible upon addition of anti-gC1qR antibody. Correspondingly, the expression of cyclin-dependent kinases (Cdk) 2/4 and cyclin E/D, as well as subsequent phosphorylation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
64
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 42 publications
6
64
0
1
Order By: Relevance
“…Various investigators previously demonstrated the immunomodulatory role of the HCV core in the inhibition of T-lymphocyte responsiveness (18,19,44,45,46). Furthermore, dendritic cell maturation and, correspondingly, their CD4 ϩ -T-cellpriming ability are impaired by the HCV core, leading to a defect in the induction of anti-HCV T cells (36,37).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Various investigators previously demonstrated the immunomodulatory role of the HCV core in the inhibition of T-lymphocyte responsiveness (18,19,44,45,46). Furthermore, dendritic cell maturation and, correspondingly, their CD4 ϩ -T-cellpriming ability are impaired by the HCV core, leading to a defect in the induction of anti-HCV T cells (36,37).…”
mentioning
confidence: 99%
“…Importantly, free core protein (non-virion associated) is secreted from infected cells and is detectable in the bloodstream of HCV-infected patients, possibly providing the virus with an indirect means of affecting host immunity (2,25,26,43). This free core protein has been shown to interfere with both proliferation and effector activities of human T cells through its interaction with a complement receptor, gC1qR, in a mixedlymphocyte reaction (18,44,45,46). However, it is not clear whether the inhibition of T-cell function by the HCV core results directly from core interactions with T cells and/or indirectly from core-induced effects on antigen-presenting cells.…”
mentioning
confidence: 99%
“…HCV infection is a serious and growing threat to human health. Its ability to efficiently establish persistent infection is postulated to be in part due to T cell suppression and is mediated via interaction between the HCV core protein and gC1qR (Yao et al, 2003), in a manner that is similar to the C1q-mediated T cell anti proliferative response reported previously (Chen et al, 1994). The specificity of the C1q-and HCV core-mediated T cell suppression was shown by inhibition studies using anti-gC1qR antibodies or by treatment of the T cells with gC1qR-silencing siRNA (Yao et al, 2003).…”
Section: Differential Cellular Localization Of Gc1qr May Dictate Its mentioning
confidence: 58%
“…Its ability to efficiently establish persistent infection is postulated to be in part due to T cell suppression and is mediated via interaction between the HCV core protein and gC1qR (Yao et al, 2003), in a manner that is similar to the C1q-mediated T cell anti proliferative response reported previously (Chen et al, 1994). The specificity of the C1q-and HCV core-mediated T cell suppression was shown by inhibition studies using anti-gC1qR antibodies or by treatment of the T cells with gC1qR-silencing siRNA (Yao et al, 2003). More recently obtained data suggest that the HCV core/gC1qR interaction arrests T cell cycle progression through stabilization of the cell cycle inhibitor p27 Kip1 , thus blocking activated T cells for the G 1 to S phase transition and inhibiting T cell proliferation (Yao et al, 2003).…”
Section: Differential Cellular Localization Of Gc1qr May Dictate Its mentioning
confidence: 58%
See 1 more Smart Citation